The effect of lean manufacturing towards financial performance at Hicom Automotive Manufacturers, Pekan, Pahang - Nor Rifhan, Hashim (2017)
Lean manufacturing plays an important role in improving employee performance and increase financial performance. This study an exploratory the relationship between the effects of lean manufacturing implementation on the financial performance. Lean manufacturing is to help the firm improve their financial performance due to this exercise can give a variety of new benefits such as cost savings, and time. In this age of development now, many firms are struggling to improve their performance along with the development of the industry, especially in the industrial and automotive industries. Therefore, this study is to prove that this relationship does actually have a positive effect on the development of the company's performance. This study was conducted in Hicom Automotive, Pekan, Pahang. This study is based on quantitative methods and using a questionnaire as a tool to collect data which has been developed by a number of instruments from previous studies. Respondents who participated in this study were employees in the management as well as human resources and finance. The respondents were 108 workers. In this study, researchers used SPSS 19 to analyze the data to measure the influence and strength of the relationship between the independent variables. Through this study, the results obtained is the relationship between lean manufacturing and the company's performance also have a positive relationship. Thus, through this study can be said lean manufacturing is something that can help improve the company's performance.